2015
DOI: 10.1007/s00066-014-0801-3
|View full text |Cite
|
Sign up to set email alerts
|

High-grade acute organ toxicity and p16INK4A expression as positive prognostic factors in primary radio(chemo)therapy for patients with head and neck squamous cell carcinoma

Abstract: P16(INK4A) expression and HGAOT are independent prognostic factors for OS of patients with HNSCC, whereas p16(INK4A) expression is particularly important for patients without HGAOT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…The prognostic impact of HPV positivity has been demonstrated by several investigations [2,5,6]. Up to now there has been little information about the influence of HPV infection on toxicity rates during combined treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The prognostic impact of HPV positivity has been demonstrated by several investigations [2,5,6]. Up to now there has been little information about the influence of HPV infection on toxicity rates during combined treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A study analyzing 233 HNSCC patients showed that p16 expression and high toxicity rates were independent prognostic factors. An interrelationship between p16 expression and radiation-induced reactions was discussed [6]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunohistochemistry of paraffin sections was carried out using an immunohistochemical double staining method including streptavidin biotinylated alkaline phosphatase (ABC-AP, DakoCytomation, Hamburg, Germany). 17,18 Each paraffin section was double stained with the following primary antibodies FoxP3-CD1, (Abcam, Cambridge, United Kingdom-DakoCytomation, Hamburg, Germany), FoxP3-CD8 + (Abcam-DakoCytomation, Fig. 1B), FoxP3-CD20 (Abcam-DakoCytomation) followed by secondary antibody.…”
Section: Treatment Protocolmentioning
confidence: 99%